The relationship of systemic inflammatory response with structural and functional changes in the myocardium in patients with pulmonary tuberculosis - D. V. Kolchin; V. I. Ruzov; L. N. Savonenkova; V. A. Razin (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Abstract. Taking into account the conflicting data on the effect of the systemic inflammatory response on the structural and functional changes in the myocardium in clinical forms of tuberculosis, we conducted an echocardiographic study and an assessment of pro- and anti-inflammatory cytokines in the blood serum.The purpose: to study the relationship of structural and functional changes in the myocardium with markers of systemic inflammation IL-6, IL-10, VEGF-A in patients with various forms of pulmonary tuberculosis.Materials and methods. The study included 77 patients with a confirmed diagnosis of pulmonary tuberculosis, who are on inpatient treatment in a tuberculosis dispensary. During the study, patients were randomized into 3 groups, cavernous form of pulmonary tuberculosis, (n = 15). The mean age of the patients was 44.2 ± 5.3 years and had no statistically significant differences between the groups. The control group consisted of 10 healthy individuals. The mean age of the control group was 42.4 ± 2.3 years. The concentration of IL-6, IL-10 and VEGF-A in blood serum was assessed by ELISA and В-mode echocardiography.The results obtained. The severity of systemic inflammation was associated with the clinical form of pulmonary tuberculosis: the maximum value of IL-6 was observed in the infiltrative form, and the minimum, but significantly higher value compared to the control group, in the fibrous-cavernous form of pulmonary tuberculosis (25, 7 ± 16.5 vs 10.3 ± 4.24). High levels of interleukin IL-6 were accompanied by higher levels of VEGF in blood serum, regardless of the form of pulmonary tuberculosis, while the highest concentration of both was observed in patients with infiltrative form of tuberculosis . A significant increase in the structural and functional values of the myocardium of the right and left parts of the heart was established both in relation to the control group and in comparison with the group of patients with an infiltrative form of pulmonary tuberculosis, despite lower levels of VEGF-A (391.43 ± 241.0 vs 274.50 ± 158.30).Conclusions. Pulmonary tuberculosis is accompanied by varying severity of systemic inflammation associated with the clinical form of the disease. Structural and functional changes in the myocardium of the right and left parts of the heart in pulmonary tuberculosis are associated with the clinical form of pulmonary tuberculosis. The most pronounced changes are observed in the fibrous-cavernous form, the minimum - in the infiltrative form. There is no direct relationship between the severity of the systemic inflammatory response and structural and functional changes in the heart.